The efficacy of curcumin/Qing Dai combination in children with active ulcerative colitis: a multicenter retrospective cohort study - Nachum, Nurit Loberman; Salomon, Nir; Yerushalmy-Feler, Anat; Weintraub, Yael; Yogev, Dotan; Granot, Maya; Haberman, Yael; Ben-Horin, Shomron; Weiss, Batia (Frontiers in Pediatrics, 2024)
Background: Curcumin and Qing Dai (QD) are herbal extracts that recently showed efficacy in treating inflammatory bowel disease (IBD). Since 2016, a combination of curcumin with QD (CurQD) has been employed in our center for management of active ulcerative colitis (UC). Objectives: We report the effectiveness and safety of CurQD therapy in children with mild-moderate UC or IBD-unclassified (IBD-U). Design: A multicenter retrospective study Methods: Children aged ≤18 years who were treated with CurQD during 2017-2021 were included. Disease activity measures were Pediatric UC Activity Index (PUCAI), and fecal calprotectin (FC). The primary outcome was a decrease in PUCAI by ≥10 points, FC normalization (≤100 µg/gr when baseline ≥300 µg/gr) or a ≥50% decrease in FC. Results: Of 30 patients (60% males, mean age 14±3.9 years), 15 (50%), 13 (43%), and 2 (7%) had pancolitis, left-sided colitis and proctitis, respectively. The daily medication dose was 0.5-3 gm QD with 1-4 gm curcumin. Concomitant treatment at induction was corticosteroids (19%), biologics (28%) and 5-aminosalicylic acid (40%). The mean duration of induction was 11.6 weeks (95% confidence interval [CI] 10.2-13.1, range 8-16). PUCAI decreased from a mean of 31.3 (95% CI 26.6- 36.0, range 5-60) to 10.9 (95% CI 7.6-14.4, range 5-35) (n=26, p<0.001). FC response and normalization occurred in 11/12 and 7/12 patients, respectively. The median decline in FC was from 749 µg/gm (interquartile range [IQR] 566-1000) to 39 µg/gm (IQR 12-132) (n=15, p=0.04). During follow-up (median 8 months, IQR 6-10), 10 patients (33%) flared; five of them regained remission or responded to a treatment change. Of 18 patients treated beyond induction, 12 (67%) achieved clinical response and 10 achieved clinical remission by the end of follow up. Conclusion: CurQD may be effective and safe as an add-on option to conventional management, for induction and maintenance in children with mild-moderate UC/IBD-U.